Water Sector Assumptions for the Shared Socioeconomic Pathways in an Integrated Modeling Framework. Issue 9 (14th September 2018) - Graham, Neal T.; Davies, Evan G. R.; Hejazi, Mohamad I.; Calvin, Katherine; Kim, Son H.; Helinski, Lauren; Miralles‐Wilhelm, Fernando R.; Clarke, Leon; Kyle, Page; Patel, Pralit; Wise, Marshall A.; Vernon, Chris R.
Abstract: The Shared Socioeconomic Pathways (SSPs) were developed without explicit assumptions for the future of the water sector; therefore, projections of future water demands based on the SSPs often lack a treatment of water technology assumptions that is consistent with the SSP storylines. This study has developed a set of qualitative and quantitative assumptions for future water sector technological advancements in the agricultural, electricity, manufacturing, and municipal sectors within the SSPs and then applied the resulting scenarios to an integrated assessment model to permit analysis of future water demand in a water‐constrained world. These scenarios are then compared to another set that excludes the adoption of water‐efficient technologies. Water demand impacts of individual SSP assumption categories are analyzed to determine scenario‐by‐scenario changes. By 2100, global annual water demands range from 3, 560 to 6, 600 km 3 . The results show that (1) technological change in the water sector can act to reduce water demand in a water limited world by up to 32% in 2100 in the SSP scenarios, (2) the most sustainable scenario produces end‐of‐century water withdrawals lower than 2010 values, (3) low‐income regions will likely be one of the largest drivers of future water demands and exhibit the greatest sensitivity to highly‐efficient water technologies, and (4) nonwater sector SSP assumptions have significant and differing impacts on demands across SSP scenarios that act to alter global water demands. Key Points: Shared Socioeconomic Pathway qualitative and quantitative model assumptions are expanded to include the water sector Future global water demand for all five SSP scenarios is analyzed with and without technological advancements in the water sector Where water supplies are constrained, global water demand reductions of up to 32% are possible in SSP scenarios by 2100